Advocate the implementation of video-assisted thoracoscopic surgery lobectomy program for early stage lung cancer treatment: time to transfer from why to how - Zhang, Hongbin; Rueckert, Jens Carsten (Annals of Translational Medicine, 2019)
Doctor Yang et al. (1) did a retrospective analysis of the National Cancer Data Base including a huge number of patients from thousands of hospitals in the United States receiving lobectomy for an early stage non-small cell lung cancer (NSCLC). As a national database, it essentially has an extraordinary multi-institutional spectrum, they compared patient characteristics, short-term and long-term 5 years survival results between the video-assisted thoracoscopic surgery (VATS) group and open thoracotomy group using the propensity score system to reduce the selection bias.